2020
DOI: 10.21315/tlsr2020.31.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Hepatopancreas and Gonads in Both Sexes of Orange Mud Crab, Scylla olivacea Cultured at Various Water Flow Velocities

Abstract: Nutritional quality of the hepatopancreas and gonads of orange portunid mud crab, Scylla olivacea was evaluated for each gender under four treatment of different water velocities (0, 20, 40 and 60 cm s −1 ), in terms of nutrient reserve and nutrient for reproduction. About 56 crabs were used in this study in which fatty acids composition was analysed using gas chromatography mass-spectrometry (GC-MS). For hepatopancreas analysis, monounsaturated fatty acids (MUFAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The fatty acid of newly hatched larvae S. olivacea was shown in Tables 14 and 15 to be influenced by the food eaten by larvae through the metamorphosis process, same with another marine crustacean (Taufik et al, 2016). Lim et al (2021), Taufik et al (2020), Waiho et al (2018) have shown that fatty acid compositions have been highlighted due to the substantial effect of essential polyunsaturated fatty acids (PUFAs) such as DHA and EPA on consumer's survival and egg production. After the nutrients were ingested, PUFA was converted into storage lipids or into structural lipids form such as cell membranes (Taufik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fatty acid of newly hatched larvae S. olivacea was shown in Tables 14 and 15 to be influenced by the food eaten by larvae through the metamorphosis process, same with another marine crustacean (Taufik et al, 2016). Lim et al (2021), Taufik et al (2020), Waiho et al (2018) have shown that fatty acid compositions have been highlighted due to the substantial effect of essential polyunsaturated fatty acids (PUFAs) such as DHA and EPA on consumer's survival and egg production. After the nutrients were ingested, PUFA was converted into storage lipids or into structural lipids form such as cell membranes (Taufik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al (2021), Taufik et al (2020), Waiho et al (2018) have shown that fatty acid compositions have been highlighted due to the substantial effect of essential polyunsaturated fatty acids (PUFAs) such as DHA and EPA on consumer's survival and egg production. After the nutrients were ingested, PUFA was converted into storage lipids or into structural lipids form such as cell membranes (Taufik et al, 2020). According to (Wang et al, 2021), EPA and DHA composition are better than C18 PUFAs to sustain the growth of crustaceans such as P. japonicus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids serve as an essential nutrient source for ovarian maturation, embryonic development, spawning, and hatching ( Peñaflorida, 2004 ). Previous studies have revealed the biochemical compositions of the edible parts of S. serrata ( Peñaflorida, 2004 ; Romano et al, 2014 ), S. olivacea ( Taufik et al, 2020 ), and S. paramamosain ( Jiang et al, 2014 ; Tantikitti et al, 2015 ). Wu et al (2020) clarified the dynamics of the biochemical composition, including lipids and amino acids, in the ovary, hepatopancreas, and muscle of S. paramamosain during the ovarian maturation period.…”
Section: Introductionmentioning
confidence: 99%